Robotic sacrocolpopexy with autologous fascia lata: A case series - Gianluca Raffaello Damiani; Mario Villa; Giovanni Falcicchio; Cristina Cesana; Antonio Malvasi; Nico Picardi; Giovanni Vergottini; Poli Piero; Miriam Dellino; Vera Loizzi; Antonella Vimercati; Ettore Cicinelli; et al. (Gynecology and Minimally Invasive Therapy, 2023)
Objectives: Apical prolapse involves the upper vagina or vaginal vault after hysterectomy. Treatment is indicated for symptomatic women, and surgical approach is considered for women who failed or refused conservative therapy. We performed 10 pickups of autologous fascia, used for robotic sacrocolpopexy (RSCP). Materials and Methods: We included patients between 60 and 80 years old who showed a Pelvic Organ Prolapse Quantification (POP-q) over the second stage and with symptoms related to prolapse. Results: All of them underwent autologous fascia lata (AFL) pickup from the right leg and after to RSCP. One patient underwent also posterior colporrhaphy. The mean intraoperative time was 199.2 min (183–230 min). No intra-operatory complications were reported. POP-q assessment during follow-up showed improvements: C point gained on average 7.6 points (5–8) and mean values went from −0.6 to − 8.2 cm (−7 to −9 cm). The three women who had anterior compartment defects shows good anatomical reconstitution with a mean Aa and Ba value of − 2.83 cm (−2.5 to −3 cm) and gained 4 points (average gain: 3.5–4.5 cm). Total vaginal lenght (TVL). Conclusion: According to these data, in our experience, AFL employment showed a good anatomical result from the first to last follow-up.